2015
DOI: 10.1021/np500809a
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory and Antileishmanial Activity of Phenylpropanoid Dimers Isolated from Nectandra leucantha

Abstract: Three phenylpropanoid dimers (1−3) including two new metabolites were isolated from the extract of the twigs of Nectandra leucantha using antileishmanial bioassay-guided fractionation. The in vitro antiparasitic activity of the isolated compounds against Leishmania donovani parasites and mammalian cytotoxicity and immunomodulatory effects were evaluated. Compounds 1−3 were effective against the intracellular amastigotes within macrophages, with IC50 values of 26.7, 17.8, and 101.9 μM, respectively. The mammali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
47
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 40 publications
(69 reference statements)
5
47
0
5
Order By: Relevance
“…The parasite burden was determined by the number of infected macrophages out of 400 cells. Compounds were tested to the highest concentration of 100 μ m and were reported as not active (>100) when the IC 50 value was above this concentration …”
Section: Methodsmentioning
confidence: 99%
“…The parasite burden was determined by the number of infected macrophages out of 400 cells. Compounds were tested to the highest concentration of 100 μ m and were reported as not active (>100) when the IC 50 value was above this concentration …”
Section: Methodsmentioning
confidence: 99%
“…Cells were treated with AmB (native drug) and nanoformulations of MTC, TC, UC and AmBisome V R equivalent to their IC 50 concentration, and untreated cells were considered as control. Supernatants were collected after 72 h of incubation at 37 C and analyzed for the concentration of cytokines (TNF-a, IL-12, and IL-6) by ELISA plate reader at 405 nm [16].…”
Section: Cytokine Elisamentioning
confidence: 99%
“…After ten min incubation, absorbance was evaluated using the ELISA plate reader at 540 nm. Results achieved were extrapolated from a standard curve plotted with NaNO 2 at different concentrations (0-400 lM) [16].…”
Section: Quantification Of Nitric Oxidementioning
confidence: 99%
“…It has also been reported that patients with active VL have higher serum levels of IL-10 and IL-6, evidencing their association with disease persistence [21]. Other studies with phenylpropanoid derivatives, demonstrated a correlation between the downregulation of IL-6 and IL-10 with the control of the infection in the Leishmania -infected macrophages [22]. Jek and co-workers [23] demonstrated that blocking NO production in rat macrophages results in an increased IL-1 and IL-6 secretion.…”
Section: Discussionmentioning
confidence: 98%